Reigns of terror - Marchak, M. Patricia (McGill-Queen's University Press, 2003)
"Reigns of Terror is a study of states that have committed gross human rights crimes against their own citizens. Patricia Marchak seeks to discover whether these states have anything in common - whether there are preconditions that can be identified as leading to crimes against humanity so that the world community could take preventive action in similar situations elsewhere. She provides short histories of nine culturally and historically diverse societies where such crimes occurred during the twentieth century, including the Ottoman Empire in Armenia, the USSR in the Eastern Ukraine, Nazi Germany, Cambodia under Pol Pot, Burundi, Rwanda, Argentina, Chile, and Yugoslavia. Marchak departs significantly from mainstream explanations of genocide, rejecting racism as a fundamental cause and disputing a wide range of other explanations that cite racist and religious ideologies, perception of threat, authoritarianism, and unique historical circumstances as primary causes. She argues that while these variables may be contributing factors, states move toward human rights crimes because their governments can no longer sustain a particular social hierarchy. Reasons for their paralysis may be economic, environmental, demographic, or purely political. In an attempt to re-establish the former status quo, they turn against groups low on the hierarchical scale, some of which may be defined in ethnic terms. If governments come into power as revolutionary forces, they may commit such crimes in order to establish a new social hierarchy. Other necessary but insufficient conditions for state crimes include the military capacity for committing mass murder, the creation of ideology that justifies such action, and the failure of independent institutions such as the mass media and universities to counter ideological and military forces. Reigns of Terror is highly accessible and aimed at an audience of senior undergraduates, graduate students, and faculty in the social sciences, as well as a more general reading public concerned about the many state-sponsored crimes against humanity still occurring in the world."--Publisher description